The "clash" of civilizations?: Or an emerging "East Asian modernity"? - Wee, C. J. Wan-Ling (Sojourn, 1996)
The author explores Samuel Huntington's well-known article, "The clash of civilizations?". According to Huntington, the current global conflicts can be thought of in terms of different "civilizations" clashing with each other. He thinks that "Confucian" and "Islamic" civilizations will be the ones increasingly taking centre stage in clashes with the West. Wee is concerned in this article with the "Confucian" aspect of Huntington's article. Wee suggests that static categories like "civilizations" are no useful way of reflecting upon clashes Huntington has in mind. (DÜI-Sen)